Fishing for floating marine litter in SE Bay of Biscay: Review and feasibility study. (November 2015) - Basurko, Oihane C.; Gabiña, Gorka; Andrés, Marga; Rubio, Anna; Uriarte, Ainhize; Krug, Iñigo
Abstract: Marine litter is one of the descriptors in the European Marine Strategy Framework Directive, which aims to achieve a healthy marine environment and make ecosystems more resilient to climate change. Most experiences have been focused upon quantifying the abundance and distribution of marine litter, on beaches in particular. Nevertheless, the continuous impact of litter on marine species, commercial activities, i.e. shipping and fishing, and the local economy are prompting scientist and stakeholders to identify additional approaches required to face this challenge. This contribution addresses the aforementioned need, by assessing the possibility of fishing vessels shifting from fish to floating marine litter (FML), during low fishing activity periods. For this purpose, the technical, environmental, and socio-economic feasibility of such a change is investigated. The technical assessment includes: the analysis of energy consumption; and the assessment of ocean surface current patterns as a tool to determine FML convergence hotspots. The environmental feasibility is analysed by a Life Cycle Assessment study of 3 FML management scenarios. The minimum subsidy required is analysed in the socio-economic assessment, in order to reach a profitable diversified activity. The results demonstrate fishing FML as a technically-, economically- and environmentally-viable activity. Nevertheless, Local Authorities need to encourage the prevention of FML arriving on shore where, in some environments, such as in rocky shores, cleaning is difficult. Highlights: Diversification of fishing activity is feasible for the artisanal fishing fleet. Technical, environmental, and economic feasibility of activity change is studied. Local authorities have a key role to play to enhance marine litter collection. Subsidy for litter collection may be more economical than waste collection services.